Enhancing Music Notation Reading in Teachers Through Kodály Method and Technological Integration - Hikmawati Usman; Andi Ichsan; Sayidiman; Hotimah; Nurfaizah A. P (The Indonesian Institute of Science and Technology Research, 2026)
This study aims to explore the application of the Kodály method in improving music notation reading skills among in-service and pre-service music teachers, as well as the challenges encountered in its implementation. The research method employed is a Systematic Literature Review (SLR), which involved 22 studies that met the inclusion criteria from a pool of 414 articles selected via a Scopus database search using the keywords “Kodaly”, “teacher music skill”, “teacher music learning”, “music literacy”, “notation learning”, “Pre-service music teachers”, “Music teaching methods”, “Music teacher training”, and “Music education curriculum”. The selection process was based on publication year criteria (2015 to 2025) and relevance to the research topic. All selected articles possessed an active DOI and were available for free download via the Scopus database using the Watase.web.id tool. From the screening process, 237 articles were removed for not meeting the criteria, and a further 98 articles were excluded as they were not classified as Q1, Q2, Q3, or Q4 journals. Following the screening, 22 articles were assessed for eligibility and included in the systematic review. The results indicate that the application of the Kodály method is effective in enhancing music notation reading skills through its sound-based, kinesthetic, and music theory approaches. However, the primary challenges in implementation were identified as a lack of adequate teacher training and limited resources in many schools. Technology and project-based approaches were found to enrich the learning experience, making the instruction more interactive and relevant to contemporary developments. This study affirms the importance of continuous training and technology integration to strengthen the teaching of the Kodály method within music education contexts.